Lexical density and readability of reading texts in English for Nusantara eight grade textbook - Basir, Amin; Nurliasari, Hanifa; Rahmansyah, Sutiadi; Hidayat, Hendi (citeus, 2025)
Reading is crucial for learning as it allows students to comprehend texts across various subjects. Effective texts play a significant role in enhancing students' reading skills. To determine suitable reading materials for students, evaluating lexical density and readability is essential. This study examines the lexical density and readability of reading passages in the “English for Nusantara” textbook used by eighth-grade students. A qualitative descriptive method and content analysis were used in this research, by analyzing 20 selected texts from each chapter of the textbook. The study aims to (1) assess the lexical density of the selected passages, (2) evaluate their readability levels, and (3) determine the relevance of these factors to the students' grade level. Lexical density was measured using Ure’s (1971) formula, while Flesch’s reading ease formula assessed readability. The findings revealed that (1) none of the texts had low lexical density; 12 texts had moderate lexical density, and 8 had high lexical density; (2) the readability test indicated five different reading levels among the 20 texts, with only 4 texts suitable for the students' grade level; and (3) the textbook may be insufficiently challenging in terms of readability, though the moderate to high lexical density suggests students are exposed to rich vocabulary.